L’instabilité structurelle dans le modèle de croissance avec ressource non renouvelable - Hung, N. (L'Actualité économique, 1981)
ABSTRACTThe analysis of the question of structural stability in the growth model with exhaustible resources consists essentially in the examination of the long term values of capital and consumption as they result from parametric variations. The parameters used in this study relate to ethic (discount rate) and to technology (elasticity of substitution between resource and capital and technical progress). Considering the structural stability, the already known results are generalized in two directions. First, a general description of production technology is made. Second, a special attention is given to the question of technological innovation. An analysis of the form of the Hicksian neutral technical progress is made considering an economy with a Cobb-Douglas production function.